Risk Factors Associated With Long-Term Hospitalization in Patients With COVID-19: A Single-Centered, Retrospective Study - Wu, Yiqun; Hou, Bingbo; Liu, Jielan; Chen, Yingying; Zhong, Ping (Frontiers in Medicine, 2020)
Background The coronavirus disease 19 (COVID-19) pandemic has become a global threat. Few studies have explored the risk factors for the recovery time of patients with COVID-19. This study aimed to explore risk factors associated with long-term hospitalization in patients with COVID-19. Methods In this study, patients with laboratory-confirmed COVID-19 hospitalized in a hospital in Wuhan by March 30, 2020 were included. Demographic, clinical, laboratory, and radiological data from COVID-19 patients on hospital admission were extracted and were compared between the two groups, defined as short- and long-term hospitalization, respectively according to the median hospitalization time. Univariable and multivariable logistic regression methods were performed to identify risk factors associated with long-term hospitalization in patients with COVID-19. Results A total of 125 discharged patients with COVID-19 were reviewed, including 123 general patients and two severe patients. The median hospitalization time was 13.0 days (IQR 10.0-17.0). Among them, 66 patients were discharged < 14 days (short-term group) and 59 patients were discharged ≥ 14 days (long-term group). Compared with the short-term group, patients in the long-term group had significantly higher levels of C-reactive protein (P=0.000), troponin I (P=0.002), myoglobin (P=0.037), aspartate aminotransferase (P=0.005), lactic dehydrogenase (P=0.000), prothrombin time (P=0.030), fibrinogen (P=0.000), and D-dimer (P=0.006), but had significantly lower levels of lymphocyte count (P=0.001), platelet count (P=0.017), albumin (P=0.001), and calcium (P=0.000). Additionally, the incidences of hypocalcemia (P=0.001), hyponatremia (P=0.021), hypochloremia (P=0.019), and bilateral pneumonia (P=0.000) in the long-term group were significantly higher than those in the short-term group. Multivariable regression showed that hypocalcemia (P=0.007, OR 3.313, 95% CI 1.392-7.886), hypochloremia (P=0.029, OR 2.663, 95% CI 1.104-6.621), and bilateral pneumonia (P=0.009, OR 5.907, 95% CI 1.073-32.521) were independent risk factors associated with long-term hospitalization in patients with COVID-19. Furthermore, a ROC curve where the area under the ROC was 0.766 for retained variables is presented. Conclusions Hypocalcemia, hypochloremia, and bilateral pneumonia on hospital admission were independent risk factors associated with long-term hospitalization in patients with COVID-19. To the best of our knowledge, this is the first study to highlight the importance of electrolyte imbalance in predicting the hospitalization time of patients with COVID-19.